2022
DOI: 10.1007/s00383-022-05344-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservative antibiotic treatment of pediatric acute uncomplicated appendicitis during the COVID-19 pandemic: a prospective comparative cohort study

Abstract: Background Our study aimed to compare the clinical outcomes and cost-efficiency of antibiotic management versus laparoscopic appendectomy for acute uncomplicated appendicitis (AUA) in children during the COVID-19 pandemic when resources were limited and transmission risks uncertain. Method In this prospective comparative cohort study, we analyzed the data of 139 children diagnosed with AUA meeting the following inclusion criteria: 5–18 years of age, symptoms duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The novel application of NOM during the initial pandemic assault has shown that NOM can be an effective management strategy [11,94,95]. When proper standards and strict patient selection criteria for applying NOM are set, informed decision making by parents can be made with acceptable cost effectiveness [9,35,42].…”
Section: Recurrent Appendicitis After Non-operative Managementmentioning
confidence: 99%
“…The novel application of NOM during the initial pandemic assault has shown that NOM can be an effective management strategy [11,94,95]. When proper standards and strict patient selection criteria for applying NOM are set, informed decision making by parents can be made with acceptable cost effectiveness [9,35,42].…”
Section: Recurrent Appendicitis After Non-operative Managementmentioning
confidence: 99%